2011
DOI: 10.1186/1471-2202-12-23
|View full text |Cite
|
Sign up to set email alerts
|

Focused ultrasound-mediated suppression of chemically-induced acute epileptic EEG activity

Abstract: BackgroundEpilepsy is a common neurological disorder, which is attributed to uncontrollable abnormal hyper-excitability of neurons. We investigated the feasibility of using low-intensity, pulsed radiation of focused ultrasound (FUS) to non-invasively suppress epileptic activity in an animal model (rat), which was induced by the intraperitonial injection of pentylenetetrazol (PTZ).ResultsAfter the onset of induced seizures, FUS was transcranially administered to the brain twice for three minutes each while unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
203
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(212 citation statements)
references
References 71 publications
8
203
0
1
Order By: Relevance
“…We have demonstrated that the pulsed application of low-intensity (i.e. lower than the intensity approved for diagnostic ultrasound imaging) focused ultrasound (FUS) on the rabbit brain modulated neural tissue excitability in a non-thermal manner [12] and reduced chemically induced epileptic states in rats [13] , all without inducing tissue/vascular damage. FUS is a technique that delivers acoustic energy to localized tissue areas (on the order of millimeters in diameter, roughly the size of a rice grain), thus allowing for the concurrent deposition of thermal or mechanical energy to a targeted tissue region [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the pulsed application of low-intensity (i.e. lower than the intensity approved for diagnostic ultrasound imaging) focused ultrasound (FUS) on the rabbit brain modulated neural tissue excitability in a non-thermal manner [12] and reduced chemically induced epileptic states in rats [13] , all without inducing tissue/vascular damage. FUS is a technique that delivers acoustic energy to localized tissue areas (on the order of millimeters in diameter, roughly the size of a rice grain), thus allowing for the concurrent deposition of thermal or mechanical energy to a targeted tissue region [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…A similar and related application is acoustic neuromodulation, where, as part of treatment for a variety of neurologic disorders, ultrasound waves are used to control neuronal activity without producing heat or cavitation (Gavrilov et al 1996;Min et al 2011;Tufail et al 2010;Tyler et al 2008). In contrast to the therapeutic objective of acoustic neuromodulation, the intention of the present work was to induce mild injury in the brain.…”
Section: Introductionmentioning
confidence: 93%
“…In a murine epilepsy model, MRgFUS has been shown to decrease epileptic activity that was induced by intraperitoneal injection of pentylenetetrazol. 63 Although further studies are warranted, neuromodulation with MRgFUS might provide clinicians with a future potential to noninvasively target a seizure focus in the brain before its permanent ablation, if needed.…”
Section: Neuromodulation and Epilepsymentioning
confidence: 99%